'If you pay, we'll operate immediately'. Issue 5 (1st October 2000) - Miller, William L; Grødeland, Åse B; Koshechkina, Tatyana Y
Abstract : Objectives—To study the attitudes of health care staff in four postcommunist countries towards taking gifts from their clients—and their confessed experience of actually taking such gifts. Design—Survey questionnaire administered to officials including health care staff, supplemented by focus-group discussions with the general public. Setting – Ukraine, Bulgaria, Slovakia and the Czech Republic. Participants—A quota sample of 1, 307 officials including 292 health care staff, supplemented by stratified national random samples of 4, 778 ordinary members of the public and in-depth interviews or focus-group discussions involving another 323. Main measurements—Explicit justifications and willingness to accept offers, reported frequency of offers, and personal confessions to accepting "money and expensive presents" as well as smaller gifts. Results—Health care staff were far more inclined than the average official or public servant to accept "money or an expensive present" if offered, far more inclined to justify asking clients for "extra payments", and far more inclined to confess that they had actually taken gifts from clients recently. Judged by their own confessions, hospital doctors were only rivalled by traffic police and customs officials for taking money or expensive gifts from their clients. Conclusions—Poor pay does not explain why doctors so often took large gifts from their clients. Moral self justification, opportunity, and bargaining power are much more effective explanations.